ENSURING COMPETITIVE ADVANTAGE THROUGH AGILE MARKETING - Mirela-Cristina VOICU (Challenges of the Knowledge Society)
Recent events have taught us that change can occur with surprising speed. Those who had the ability to adapt to these changes continued to operate and succeed. The success of these companies was determined, among other things, by the speed of reaction to change. The rapid changes in the market impose an increasingly acute need for a marketing activity that is more agile by the day, translated into a reaction to change at least as fast by marketers. The competitive advantage belongs to those marketers and brands who can plan faster, experiment more effectively, and constantly adapt in order to accelerate success. Today's society has become much too complex to be stabilised, structured and forecasted so agile marketing is quickly becoming a requirement for successful business operations. Agile marketing is a new approach in the field of marketing management based on a series of practices aimed at solving the rigidities of traditional marketing. Agile marketing is the current way of doing marketing in volatile markets with informed consumers and fast-reacting competition. Agile principles can support companies of any size by allowing large projects to be broken down into distinct units, continuous improvement of results, and rapid adaptation in response to internal or external environment changes. In this context, the following paper reveals important aspects regarding the methodology and instruments of agile marketing to serve as a guide in incorporating agile practices into the marketing planification process in order to achieve changing business goals more efficiently.